Gender Differences in Tonic and Phasic Electrodermal Activity Components - Bari, Dindar S. (Science Journal of University of Zakho, 2020)
Electrodermal activity (EDA) is a well-established psychophysiological measurement for research and clinical approaches. Males and females often display different physiological responses to stimuli, which can be detected by EDA recordings. Using a new method to measure skin conductance (SC), skin potential (SP) and skin susceptance (SS) simultaneously at the same electrode, these differences were investigated. SC, SP, and SS were recorded from 60 participants during relaxation and stress. It was found that both tonic and phasic EDA parameters indicated gender differences. In addition, females displayed greater tonic and phasic EDA parameters (except for skin potential responses (SPRs)) than males under both relaxation and conditions of stimulation (stress). However, these results were not statistically significant (p > 0.05). This suggests that it is perhaps important to consider gender or at least note type of gender in EDA researches, but this cannot be generalized to clinical approaches.